Designing high efficiency glow discharge cleaning systems. (May 2019) - Canton, A.; Cavazzana, R.; Grando, L.; Spolaore, M.; Zuin, M.
Highlights: The profile of ion current at the wall, measured during glow discharge cleaning by electrostatic probes embedded in the wall tiles of RFX-mod, has been characterized with respect to anode design and operating conditions. Profile was found to peak around the anodes at small anode size and high and in-vessel pressure. Profile proved to be unaffected by anode radial position in the poloidal section and by anode material. Intermediate in-vessel pressure was found to be the most convenient regime to get high current glow discharge. Abstract: In this paper we present our studies about the choices of anode design and operational regime in order to get high efficiency glow discharge cleaning of the first wall of a fusion device. We analyzed a database of toroidal and poloidal profiles of the ion current density at the wall, measured by electrostatic probes embedded in RFX-mod first wall tiles, taken in different configurations. The ion current at the wall, both global and local, is in fact strictly connected to the cleaning efficiency, since during glow discharge the wall is physically sputtered by the ions. We found that small size anodes and high in-vessel pressure lead to the peaking of the current profile around the anodes locations, and we experimentally characterized this effect. Instead, we found that anode radial position in the poloidal section has negligible effect on current density profile, even when the anodes are placed at the first wall. Finally, the most convenient operational regime, in terms of pressure and current, has been proposed.